Pengaruh Penambahan Virgin Coconut Oil dan Vitamin C dalam Pengencer Sari Buah Semangka Kuning Telur Terhadap Kualitas Spermatozoa Babi Landrace - Padalani, Daniel; Marawali, Aloysius; Kune, Petrus; Uly, Kirenius (Animal Agricultura, 2025)
This study aims to find the best combination. diluent of watermelon juice and egg yolk to maintain the quality of landrace pig spermatozoa. Semen is accommodated twice a week from one two-year-old male landrace pig. This study was experimental using a Complete Randomized Design (CRD) consisting of five treatments and five repeats. The treatment consists of P0= SBS 80%+KT 20%. P1= SBS 80%+KT 20%+VCO 1.5%. VIT C 0.1 mg/mL. P2= SBS 80%+KT 20%+VCO 3.0%. VIT C 0.2 mg/mL. P3= SBS 80%+KT 20%+VCO 4.5%. VIT C 0.3 mg/mL. P4=   SBS 80%+KT 20%+VCO 6.0%. VIT C 0.4 mg/mL. Diluted semen is stored in  a coolbox at a temperature of 15-20ºC. then observed every 8 hours until the percentage of spermatozoa motility is 40%. The results of this study showed that semen diluted using watermelon juice in P1 treatment (VCO 1.5% and vitamin C 0.1%) had higher quality (P<0.05) compared to other treatments. namely motility reaching motility (53.75±4.79). viability (59.75±5.56). abnormalities (3.75±0.29). and survival (29.50±0.82 hours). It was concluded that the addition of 1.5% VCO and 0.1% vitamin C to watermelon juice diluent was effective in maintaining the quality of landrace pig spermatozoa.